Fabrication of a multi-dimensional CoFeOx catalyst for the efficient catalytic oxidation elimination of o-dichlorobenzene. (31st May 2022) - Wu, Shixing; Zhao, Haijun; Tang, Zhicheng; Zhang, Jiyi
Abstract : Multi-dimensional CoFeO x /CoO x with a 2D/1D structure exhibited outstanding catalytic activity and thermal stability in the catalytic elimination of o -DCB. Abstract : In this study, we constructed multi-dimensional CoFeO x catalysts for the catalytic oxidation elimination of o -dichlorobenzene ( o -DCB). The dimension of the catalyst was modulated to promote the dispersion of components and thus improve the surface active oxygen species. The effects of the multi-dimensional CoFeO x catalysts on surface active oxygen species and the o -DCB elimination performance were investigated. The temperatures of o -DCB catalytic oxidation with 90% conversion ( T 90 ) over the 2D/1D CoO x /CoFeO x, 2D CoFeO x and 2D/1D CoFeO x /CoO x catalysts were 395, 405, and 365 °C, respectively. The results showed that the oxygen vacancies of the 2D/1D CoFeO x /CoO x catalysts were enhanced due to the multi-dimensional effect compared to 2D CoFeO x . The outstanding catalytic activity and thermal stability of 2D/1D CoFeO x /CoO x were mainly attributed to its large specific surface area, pore volume and pore size, more Co 3+ content, excellent reducibility, large number of surface adsorbed oxygen (Osur ) species and rich oxygen vacancies.